Wearable ankle activity monitor overestimates energy expenditure during ecological walking tasks in individuals with stroke and healthy adults. - Guediri, Amine; Compagnat, Maxence; Baillargeat, Mathilde; Firmin, Lucas; Daviet, Jean-Christophe; Mandigout, Stéphane (International Journal of Rehabilitation Research, 2026)
Assessment of physical activity intensity is essential for guiding rehabilitation after stroke. Wearable activity monitors are used to estimate energy expenditure during walking; however, their validity in stroke populations under real-life walking conditions remains uncertain. This study aimed to evaluate the validity of an ActiGraph GT3X for estimating energy expenditure during walking tasks in stroke survivors using indirect calorimetry as the reference method. Thirty stroke survivors and 30 healthy controls performed indoor and outdoor walking tasks, including overground walking, stair ascent and descent, irregular terrain walking, and uphill and downhill walking. Energy expenditure expressed in metabolic equivalents was measured using the ActiGraph GT3X worn at the ankle and a portable gas exchange analyzer. Agreement between methods was assessed using Bland–Altman analyses and linear regression models. The ActiGraph GT3X overestimated energy expenditure across most walking tasks in both groups, with percentage differences ranging from 25.7 to 112% in stroke survivors and from 18.1 to 149.1% in healthy controls. In stroke survivors, walking speed was significantly associated with the difference in energy expenditure (ActiGraph GT3X – indirect calorimetry) across most tasks, with higher speeds leading to greater overestimation (e.g. β = 9.01, P  < 0.001, R 2 = 0.41 for stair descent). In healthy controls, this association was observed only for selected tasks, including overground walking and stair descent. These findings indicate that the ActiGraph GT3X has limited validity for energy expenditure estimation during ecological walking tasks. Although the device may provide relative indicators of effort, its outputs should be interpreted with caution.